Eating habits and knowledge of nutrition status among medical students of Medical Faculty, Udayana University - Dharsheinee K Vijayan; Luh Seri Ani (DiscoverSys Inc., 2019)
Introduction: Nutrition is the consumption of food, considered about the body’s dietary essentials. Excellent nutrition is a sufficient, well-balanced diet joined with regular physical activity which is a foundation for satisfying health. On the other hand, poor nutrition can lead to low immunity, amplified susceptibility to diseases, impaired physical and mental development, and decreased productivity.Method: This cross-sectional study was conducted on students of the medical faculty in University Udayana. There were 100 students were participated in this study, and they were divided into two groups. Of the total study participants, 50 were male, and 50 were female. They were asked to fill up a self-administered questionnaire. The variables that will be seen in this research is as follows; age, gender, weight, height, nutrition status, eating habit and knowledge.Result: Majority of the respondents had fair to adequate knowledge of nutrition. However, the students have a poor eating habit.Conclusion: Though the overall knowledge and nutrition status among the students were good, few minorities of the students held some misconceptions. On the other hand, the students have poor eating habits.